2009 IEEE 12th International Conference on Computer Vision 2009
DOI: 10.1109/iccv.2009.5459413
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale privacy protection in Google Street View

Abstract: The last two years have witnessed the introduction and rapid expansion of products based upon large, systematically-gathered, street-level image collections, such as Google Street View, EveryScape, and Mapjack. In the process of gathering images of public spaces, these projects also capture license plates, faces, and other information considered sensitive from a privacy standpoint. In this work, we present a system that addresses the challenge of automatically detecting and blurring faces and license plates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(131 citation statements)
references
References 12 publications
0
130
0
1
Order By: Relevance
“…The growing ubiquity of mobile imaging devices has led to applications in various environments, for example, autonomous navigation in urban settings, vision based indoor assistance for mobile robots [13], and so on. In particular, the proliferation of online databases has led to the necessity to recognize and obscure text in street level imagery for privacy protection [14].…”
Section: Introductionmentioning
confidence: 99%
“…The growing ubiquity of mobile imaging devices has led to applications in various environments, for example, autonomous navigation in urban settings, vision based indoor assistance for mobile robots [13], and so on. In particular, the proliferation of online databases has led to the necessity to recognize and obscure text in street level imagery for privacy protection [14].…”
Section: Introductionmentioning
confidence: 99%
“…From a practical perspective, storm drain inlet locations could be collected as part of drainage maintenance work or other regular work that is carried out on roads. Alternatively, an automated process could be developed allowing for a detection of storm drain inlet locations based on photo-interpretation of the application of Google Street View images, similar to algorithms that are applied for face or license plate recognition [40].…”
Section: Discussionmentioning
confidence: 99%
“…One can easily spend days to weeks tweaking parameters. Another drawback of Viola and Jones' method is that only greyscale images are processed as opposed to recent approaches that have shown that color information may improve face detection results ( [45]). To overcome these drawbacks we present two major adaptions to the OpenCV system: Firstly, we introduce new feature layers that can be used either for color channels or arbitrary descriptors and secondly, we parallelize the complete training procedure to run on many-core architectures.…”
Section: Enhanced Adaboost Trainingmentioning
confidence: 99%